1994
DOI: 10.1111/j.1432-1033.1994.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the Pre‐β‐amyloid Protein by Cathepsin d is Enhanced by a Familial Alzheimer's Disease Mutation

Abstract: A major pre-P-amyloid proteinsps (APP,,,) processing activity from Alzheimer's disease brain extracts was identified and found to be indistinguishable from the activity of cathepsin D.APP,, processing activity cleaved APP,,, into a series of fragments that reacted on immunoblots to a monoclonal antibody (C286.8a) against p-amyloid-( 1 -7)-peptide and cleaved N-dansyl-APP-(591-601)-amide at the Glu-Val and Met-Asp bonds. Fragments of 5.5 kDa and 10-12 kDa were formed from the cleavage of APP,,, by cathepsin D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 37 publications
(20 reference statements)
1
33
2
Order By: Relevance
“…Another analysis method which can provide more precise data on the cleavage positions is electrophoresis followed by blotting and protein sequencing, which was taken by Dreyer et al [48] with the full length APP substrate. For a full analysis of all cleavage positions in a protein or large peptide, the classical Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis method which can provide more precise data on the cleavage positions is electrophoresis followed by blotting and protein sequencing, which was taken by Dreyer et al [48] with the full length APP substrate. For a full analysis of all cleavage positions in a protein or large peptide, the classical Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…A further acceleration of APP processing is expected if, as we observed, the trafficking to endosomes of appropriate proteases is increased abnormally. In this regard, one of the cathepsins that we monitored in this study, Cat D, has ␤ and ␥ secretase activity toward model peptides and/or recombinant APP (Dreyer et al, 1994;Evin et al, 1995;Higaki et al, 1995;Chevallier et al, 1996). Other cathepsins also indirectly influence A␤ formation (Sahasrabudhe et al, 1993;Bernstein and Wiedanders, 1994;Munger et al, 1995).…”
Section: Implications For ␤-Amyloidogenesis and Pathogenesis In Admentioning
confidence: 99%
“…Our previous studies (Nixon and Cataldo, 1993;Cataldo et al, 1995Cataldo et al, , 1996 of AD brain revealed a marked upregulation of lysosomal activity at an early stage in the metabolic compromise of neurons within affected regions, including marked upregulation of acid hydrolase synthesis and two-to sevenfold increases in the numbers of lysosomes. The accumulation of various acid hydrolases within late endosomes and lysosomes, including proteases with potential APP secretase activities such as cathepsins B and D (Tagawa et al, 1991;Nixon and Cataldo, 1993;Dreyer et al, 1994;Cataldo et al, 1995Cataldo et al, , 1996Evin et al, 1995), the release of these enzymes after neuronal lysis (Nixon and Cataldo, 1993;Cataldo et al, 1994Cataldo et al, , 1995Cataldo et al, , 1996, and their persistence extracellularly in association with A␤ deposits (Nixon and Cataldo, 1993;Cataldo et al, 1994Cataldo et al, , 1995Cataldo et al, , 1996, has been observed only in disorders in which A␤ is accumulated, suggesting a link between E-L system abnormalities and ␤-amyloidogenesis.…”
Section: Abstract: Endocytosis; Early Endosome; Protease; Neurodegenmentioning
confidence: 99%
“…Calpain I has been shown to Zhao et al (1995) cleave both soluble and membrane-bound /IAPP at three distinct cleavage sites; however, none of these sites corresponds to the N-terminus of A/I . Cathepsin U has been shown to cleave the native /IAPP substrate generating the appropriatelength fragments (Sahasrabudhe et al, 1993;Savage et al, 1994); EC 3.4.24.15 and cathepsin D have been reported to cleave purified recombinant human /IAPP to generate a 15-or 12-kDa amyloidogenic CT, respectively (Dreyer et al, 1994;Papastoitsis et al, 1994). It is possible that substantial amounts of /IAPP expressed in cells are metabolized into nonamyloidogenic fragments as long as lysosomal proteases function normally but that potentially amyloidogenic fragments start to accumulate when lysosomal protease activities are lowered .…”
Section: Generation Of Amyloidogenic Ct Fragmentsmentioning
confidence: 99%